Study the effect of sliding frequency on reciprocating sliding wear test for titanium alloy Ti-6Al-4V - Mohd Harun, Dalila; Thenan, Thamil; Ahmad Nordin, Nurani; Mohd Tobi, Abd Latif; Jamian, Saifulnizan; Marsi, Noraini (Penerbit UTHM, 2020)
Titanium alloys are widely used in the aerospace, automotive, chemical and biomedical industries. Titanium and its alloys have excellent corrosion resistance towards many of the highly corrosive environments, particularly, oxidizing and chloride containing process streams due to their excellent combination of low density, high strength to weight ratio, corrosion resistance and biocompatibility (Feng & Xu, 2006). This material have evoked sufficient interest among tribologists due to their poor performance when subjected to wear (Argatov, 2011); (Chen & Zhou, 2001). Tribo contact between uncoated titanium alloy once the coated completely used are crucial and these need to be study and analyse.